The effect of using english blog on students’ writing ability in narrative text at tenth grade of MAN Labuhanbatu - Rambe, Shopiah Anggraini; Harahap, Anna Leli; Yulianda, Asri; Harahap, Adinda Ulandari (Universitas Lampung, 2022)
The objective of this research is the effect of using English blog on students’ writing ability in narrative text at tenth grade of MAN Labuhanbatu in the Academic Year 2020/2021. This research is quantitative experimental research methods. The design used in this research quasi experimental and used the Nonequivalent Control Group Design model. The sample used is purposive sampling from 4 classes X MIPA. The sample was used is X MIPA 1 as experiment class and X MIPA 2 as control class which has a subject 71 students. Instrument for collecting data were the tests namely pretest and posttest. The results of this research show that used of using English blog was there is any effect on student’s writing at MAN Labuhanbatu in the academic year 2020/2021. The researcher found out that increasing of experimental class which got mean 65.8 on pretest and got mean 74.4 on posttest. Because t count value higher than t table (2.969 > 1.667), means it Ha is accepted and Ho is rejected. Keywords: Using English Blog, Writing Ability